The empathic bases of moral behaviour // DOI: 10.18226/21784612.v22.n.especial.01 - Silveira, Matheus de Mesquita (CONJECTURA: Filosofia e Educação, 2017)
This article aims to examine the possibility to explain the basis of moral behaviour in natural terms consistent with evolutionary theory. The defense position begins with the clarification of the concept of empathy, as done by Hume and Darwin, plus contemporary research in the areas of neuroscience, evolutionary psychology and ethology. My argument points in favor of the hypothesis that socially relevant emotions are regulators of social behaviour, being a criterion for distinguishing between moral and purely social relations. What should be understood is in that bases psychobiological mechanisms of sociability, particularly empathy and social instincts, operate as regulators of normative behaviour in small groups and how this relates to the way moral distinctions are made in everyday life. The focus of this investigation will be to identify the elements that are at the root of such behaviour and explain it without resorting to metaphysical concepts. I will present empathy as the candidate to answer the question of how these mechanisms developed within the evolutionary process and how to add an intersubjective element to social relevant emotions, so that they have the strength to inhibit socially relevant behaviours. Key-Words: Empathy. Social Instincts. Moral Behaviour.